Availability of energetic substrates and exercise performance in heart failure with or without diabetes - Melenovsky, Vojtech; Kotrc, Martin; Polak, Jan; Pelikanova, Terezie; Bendlova, Bela; Cahova, Monika; Malek, Ivan; Jarolim, Petr; Kazdova, Ludmila; Kautzner, Josef (European journal of heart failure, 2012)
AIMS: The goal of the study was to examine whether resting or post-exercise metabolic substrate levels are associated with differential exercise performance and long-term outcome in control subjects or heart failure (HF) patients with or without type 2 diabetes mellitus (DM). METHODS AND RESULTS: Twenty five healthy controls matched with 97 patients with stable advanced HF were prospectively enrolled. Exercise capacity, age, gender, and HF aetiology were balanced between HFDM- and HFDM+ groups. Subjects underwent maximal bicycle spiroergometry with blood sampling to measure metabolites and neurohormones before and immediately after the exercise. HFDM+ patients had increased free fatty acids, glucose, and β-hydroxybutyrate compared with controls. HFDM+ patients had higher baseline copeptin (24 ± 16 vs. 17 ± 13 pmol/L, P < 0.05) but otherwise showed similar neurohumoral activation and exercise response to HFDM- patients. Peak oxygen consumption (VO(2)) was unrelated to post-exercise free fatty acids, glucose, lactate, or glycerol, but strongly correlated with post-exercise pyruvate (in all: r = 0.62, P < 0.001). During the next 17 ± 10 months, 36% of HF patients experienced an adverse event (death, urgent transplantation, or assist device insertion). From metabolic factors, only post-exercise glucose [hazard ratio (HR) 1.28, P = 0.04), total body fat (HR 0.58, P < 0.001), and the presence of DM (HR 1.98, P = 0.04) were predictive of the outcome. CONCLUSIONS: With the exception of pyruvate, acute changes of metabolic substrates are not related to cardiac performance in HF, regardless of diabetic status. Inhibition of body fat depletion, attenuation of stress-related hyperglycaemia, or increasing dynamics of plasma pyruvate may represent therapeutic targets in advanced HF.
Keywords: Analysis of Variance; Statistics as Topic; Exercise Tolerance; Female; statistika jako téma; ženské pohlaví; Heart Failure; Diabetes Mellitus, Type 2; Fatty Acids, Nonesterified; Oxygen Consumption; lidé; srdeční selhání; cvičení; diabetes mellitus 2. typu; studie případů a kontrol; Humans; analýza rozptylu; prospektivní studie; Male; Case-Control Studies; Prospective Studies; glukosa; Exercise Test; kyseliny mastné neesterifikované; Glucose; Insulin Resistance; inzulinová rezistence; tolerance zátěže; lidé středního věku; mužské pohlaví; Exercise; Middle Aged; spotřeba kyslíku; zátěžový test